2021
DOI: 10.1111/ajt.16416
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity in kidney transplant recipients is similar to nontransplant patients with similar comorbidities

Abstract: Higher rates of severe COVID‐19 have been reported in kidney transplant recipients (KTRs) compared to non‐transplant patients. We aimed to determine if poorer outcomes were specifically related to chronic immunosuppression or underlying comorbidities. We used a 1:1 propensity score‐matching method to compare survival and severe disease‐free survival (defined as death and/or need for intensive care unit (ICU)) incidence in hospitalized KTRs and non‐transplant control patients between 26 February and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 30 publications
6
79
1
6
Order By: Relevance
“…Another interesting observation is made in the work of Chavarot et al Here, transplanted patients with COVID-19 disease were matched with other COVID-19 patients who had similar chronic comorbidities and the course of COVID disease was studied. The results showed a similar mortality rate in both collectives, so Chavarot et al concluded that the severity of COVID-19 disease was not associated with immunosuppression but with the comorbidities [ 16 ]. This conclusion confirms results already published in November by Chaudhry et al [ 17 ].…”
Section: Discussionmentioning
confidence: 93%
“…Another interesting observation is made in the work of Chavarot et al Here, transplanted patients with COVID-19 disease were matched with other COVID-19 patients who had similar chronic comorbidities and the course of COVID disease was studied. The results showed a similar mortality rate in both collectives, so Chavarot et al concluded that the severity of COVID-19 disease was not associated with immunosuppression but with the comorbidities [ 16 ]. This conclusion confirms results already published in November by Chaudhry et al [ 17 ].…”
Section: Discussionmentioning
confidence: 93%
“…Centers for Disease Control (CDC) claims that 8 out 10 COVID-19 death in the U.S. has been reported in adults aged more 65 years and the risk of hospitalization and death increases enormously with age. [32] The effect of immunosuppression is still controversial in KT recipients [33]. Immunosuppression is known to dysregulate innate and adaptive immunity, exposing the patients to severe infections.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several multicenter studies evaluated the effect of immunosuppression on outcomes from COVID-19, none of which found an association between immunosuppression and mortality from COVID-19. 9,11,13 Compared with nontransplant patients, kidney transplant recipients are at greater risk of developing AKI (46.1% vs 11.2%, P < .001). 14 After matching comorbidities and age, severe disease incidence was similar between kidney transplant recipients and nontransplant patients; however, mortality was higher for kidney transplant recipients (17.9% vs 11.4%, P = .038).…”
Section: Discussionmentioning
confidence: 99%
“…12 Several multicenter studies evaluated the effect of immunosuppression on outcomes from COVID-19, none of which found an association between immunosuppression and mortality from COVID-19. 9,11,13…”
Section: Covid-19mentioning
confidence: 99%